Structural Evolution of Mn-Based Disordered Rock Salt Cathodes - Li, Tianyu; Geraci, Tullio Salvatore; Koirala, Krishna Prasad; Wang, Chongmin; Navrotsky, Alexandra; Clement, Raphaele J (Meeting abstracts (Electrochemical Society), 2024)
Manganese-based disordered rock salt (DRX) oxides are promising new generation lithium-ion cathode materials due to the low costs and the high theoretical capacities. Recent research has revealed that DRX compounds with high manganese content, denoted as Li 1+x Mn y M 1-x-y O 2 (where y>0.5 and M represents hypervalent d0 ions such as Ti 4+ and Nb 5+ ), undergo a gradual capacity increase over initial charge-discharge cycles. This phenomenon coincides with the development of localized domains exhibiting a spinel-like cation arrangement within the overall disordered structure, termed the "δ phase." In my presentation, I will detail our effort on systematically investigating the structural changes occurring in manganese-based DRX compounds at various levels of lithium removal through heating. Analysis using synchrotron X-ray, neutron diffraction and 7 Li solid state NMR reveals that , during the structural relaxation of delithiated DRX, lithium and manganese/titanium cations selectively migrate to different crystallographic sites within the rock salt structure, driving the observed structural rearrangements. We confirm that the structural evolution is the major factor contributing to the capacity enhancement. Furthermore, our research shows that both manganese-rich and manganese-poor DRX oxides can undergo thermal relaxation into the δ phase at delithiated states. However, the relaxation processes in DRX with different Mn content result in distinct domain structures. Calorimetry measurements and in-situ heating XRD experiments suggest that the structural relaxation exhibits a stronger thermodynamic driving force and lower activation energy for manganese-rich DRX compounds compared to manganese-poor systems. This difference explains why the observed structural evolution occurs predominantly in the former category during battery cycling. Figure 1